Scoping review of medical students' perceptions of the field of dermatology - Rewan Abdelwahab; Ahmad Shahin; Yong‐hun Kim; Jennifer Coias; Muhammad B. Qureshi; Nahid Vidal (Wiley, 2023)
Abstract Background Although perceived barriers to applying to dermatology have been researched among medical students, there remains a dearth of literature dedicated to understanding perceptions that medical students have of the field of dermatology and dermatologists. Methods A review of the literature in Embase, Pubmed, Scopus, Web of Science, and ScienceDirect were carried out to identify articles and abstracts between 2016 and 2021 relating to medical student perceptions of the field of dermatology. Peer‐reviewed English studies measuring attitudes/level of interest in dermatology or other specialities, understanding of dermatologic topics, procedures, and/or scope of practice were included. Duplicate studies and conference abstracts were excluded. All publications were screened using the PRISMA‐Sc guidelines. Findings were summarised and tabulated accordingly. Results A total of nine articles met inclusion criteria and eight are included in this review since one was not accessible online. Notable findings include non‐US medical students perceiving dermatology as monotonous, stigmatized, unfamiliar, and difficult to access with a misunderstanding of the diversity and severity of the conditions dermatologists treat. No data on US medical student perceptions was found. Perceptions were found to be influential in career planning: medical students may reject specialities after exposure to negative comments on the field. Factors attracting students to dermatology include the appeal of being a dermatologist, media portrayal, and dermatologists' influence on patients' lives. Completion of dermatology‐related activities improved medical student interest, comfort, and understanding of the field. Early dermatology exposure in US undergraduate premedical students led to heightened interest in the field, more confidence in ability to find dermatology mentors, and increased perception that dermatology serves the needs of underserved communities. Conclusions This review demonstrates the need to further investigate medical student perceptions of dermatology, particularly in the United States. Perceptions of medical specialities can impact medical student career choices. Understanding which misconceptions may be preventing students from exploring dermatology can inform efforts towards improving diversity, equity, and inclusion: translating to an equitable match and improving patient outcomes. Limitations include exclusion of articles published before 2016, geographic variability in studies, and limited data on evolving student perceptions over time.